2014
DOI: 10.1001/jamasurg.2014.1393
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Palliative Care Consultations Over Time in Relationship to Systemwide Frailty Screening

Abstract: Our data suggest that a systematic frailty-screening program effectively identifies at-risk surgical patients and is associated with a significant reduction in mortality for patients undergoing palliative care consultation. Analysis also suggests that preoperative palliative care consultations ordered by surgeons are associated with reduced mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 15 publications
1
73
0
Order By: Relevance
“…While availability of palliative care specialists is a problem in some settings, 33 low consultation rates by surgeons might also be due to negative views of their utility. 34 Our findings support the need to improve collaboration between these clinicians, and to develop new models of effective surgical/palliative care teamwork. In addition, surgeons would benefit from basic palliative care education to better fulfill their role as primary palliative care providers specifically in areas of perioperative discussions, decision management, and goal setting.…”
Section: Discussionsupporting
confidence: 64%
“…While availability of palliative care specialists is a problem in some settings, 33 low consultation rates by surgeons might also be due to negative views of their utility. 34 Our findings support the need to improve collaboration between these clinicians, and to develop new models of effective surgical/palliative care teamwork. In addition, surgeons would benefit from basic palliative care education to better fulfill their role as primary palliative care providers specifically in areas of perioperative discussions, decision management, and goal setting.…”
Section: Discussionsupporting
confidence: 64%
“…In a previously published subgroup analysis of 310 of these patients receiving palliative care consultations, we controlled for whether patients underwent surgery, and the survival benefit remained robust (odds ratio of dying after FSI implementation, 0.37; 95% CI, 0.22-0.62). 15 These results also provide estimates of the likely rates of postoperative mortality over time at different levels of frailty, and these estimates have potential to inform the shared decision making between surgeons and patients. For example, patients with RAI scores between 26 and 30 have associated mortality risks of 20.3% at 6 months, increasing to 32.0% at 1 year.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, by applying the proportionality concept, some clinical investigations have shown that an early palliative care consultation in specific acute situations as decompensated severe chronic obstructive pulmonary disease (COPD), 15 metastatic non-small cell lung cancer, 16 and frail patients with acute surgical pathology is associated with fewer interventions, a higher survival time and, not less important, with improved quality of life. 17 In conclusion, survival of critically ill patients has remarkably improved, 18 resulting in survival of patients with severe disabilities in need of continued assistance and multidisciplinary care for a long period of time, situation known as the post-ICU syndrome. Some patients, especially those with severe underlying conditions, such as advanced heart failure (NYHA III -IV), advanced COPD (Gold IV), metastatic malignant neoplasms, frail elderly patients and others must have their life-values and end--of-life preferences assessed ideally before, but also after acute critical illness onset.…”
mentioning
confidence: 99%